Early stimulation in female heads of household - Cruz García Lirios (Universitas Negeri Makassar, 2021)
The exploration of the structure of relations between variables that explain the process of early stimulation was the objective of the present work. A non-experimental study was carried out with a non-probabilistic selection of 100 students, considering their participation in a family planning and entrepreneurship program. A composition of eight factors was found: values, beliefs, perceptions, knowledge, abilities, attitudes, intentions and behaviors that explained 45% of the total variance, but the design of the research limited the findings to the scenario suggesting the inclusion of factors that Literature identifies as parenting styles in terms of volitional theories.